Pesantren Masa Depan: Paradigma Pendidikan Islam Paduan Tradisional-Modern Terintegrasi - Binti Nur Afifah; Fahad Asyadulloh (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2021)
The discourse about building an educational paradigm that is suitable for application in pesantren institutions is still interesting to discuss. Many conceptual offers have been presented. This is closely related to the role of pesantren in the modern era with its complexities and problems. Traditional and modern Islamic boarding schools are considered inadequate in responding to the challenges of the times between pragmatic needs and the fulfillment of the moral-spiritual dimension. For this reason, this article intends to offer a pesantren education paradigm that combines traditional and modern components. That the integrated paradigm based on al-Muhafazah 'ala al-Qadim al-Salih wa al-Akhd bi al-Jadid al-Aslah is expected to be able to alleviate the complexity of the education system implemented in Islamic boarding schools. At the very least, this offer is the first step towards a future pesantren with the spirit of salih li kulli zaman wa al-makan; have sensitivity and care about the development of the world. In turn, they are able to produce competent individuals, both in the field of faith and piety and also competence in the field of science and technology (science and technology).